Cultural Competence Training for Clinical Staff: Measuring the Effect of a One-Hour Class on Cultural Competence. (April 2013) - Delgado, Deborah Ann; Ness, Sheryl; Ferguson, Kathy; Engstrom, Patricia Lorraine; Gannon, Theresa M.; Gillett, Craig
In an environment of changing demographics and health care disparities, it is essential that nurses continue to develop competence in providing care across cultures. This article presents the findings of a pilot project to measure and compare self-reported cultural competence scores before and after participation in one of the core classes of a cultural competence curriculum. Cultural competence of the staff of a patient care unit ( N = 98) was assessed prior to the class, at 3 months, and at 6 months posteducation using the Inventory for Assessing the Process of Cultural Competence Among Healthcare Professionals–Revised. The results demonstrated that following an educational intervention the participants self-reported a statistically significant increase ( p = .03) in cultural competence within the category range of cultural awareness. Providing cultural competence education may better equip nurses to care for patients from diverse cultures.